Methylation of the NT5E Gene Is Associated with Poor Prognostic Factors in Breast Cancer - Young Ju Jeong; Hoon Kyu Oh; Hye Ryeon Choi; Sung Hwan Park (Diagnostics, 2020)
Cluster of differentiation (CD) 73, which is encoded by the NT5E gene, regulates production of immunosuppressive adenosine and is an emerging checkpoint in cancer immunotherapy. Despite the significance of CD73 in immuno-oncology, the roles of the NT5E gene methylation in breast cancer have not been well-defined yet. Therefore, we aimed to investigate the prognostic significance of the NT5E gene methylation in breast cancer. The DNA methylation status of the NT5E gene was analyzed using pyrosequencing in breast cancer tissues. In addition, the levels of inflammatory markers and lymphocyte infiltration were evaluated. The mean methylation level of the NT5E gene was significantly higher in breast cancer than in normal breast tissues. In the analysis of relevance with clinicopathologic characteristics, the mean methylation levels of the NT5E gene were significantly higher in patients with large tumor size, high histologic grade, negative estrogen receptor expression, negative Bcl-2 expression, and premenopausal women. There was no difference in disease-free survival according to the methylation status of the NT5E gene. We found that the NT5E gene methylation was related to breast cancer development and associated with poor prognostic factors in breast cancer. Our results suggest that the NT5E gene methylation has potential as an epigenetic biomarker in breast cancer.